Multi-generational effects under single and pulse exposure scenarios in two monophyletic Daphnia species - Araujo, G. S.; Abessa, D. M. S. [UNESP]; Soares, A. M. V. M.; Loureiro, S. (Elsevier B.V., 2019)
Anthropogenic activities commonly relate to a set of diffuse and point contamination sources, from industrial, domestic or agricultural outputs, characterized by a chemical cocktail exposure and consequent disturbances of natural ecosystems. Different species may present different sensitivities to contaminants, even when phylogenetically close. This study used two monophyletic Daphnia species from tropical and temperate environments, Daphnia similis and Daphnia magna respectively, to evaluate the variation of their sensitivity to Pb (if any) and fitness during a multi-generational exposure and recovery. To accomplish that, standard acute immobilization tests were done on specific generations. Tests were carried out with exposures to 1) potassium dichromate (K2Cr2O7) to evaluate organisms' sensitivity/fitness, 2) Pb, to monitor variation on Pb sensitivity and 3) the fungicide mancozeb, providing a pulse toxicity approach on generational Pb acclimated daphnids. Since growth is an important trait related to organisms' fitness, organisms' size measurements were also monitored. In addition, organisms were maintained under two different dietary regimes. Our results indicate no variation on daphnids sensitivity to K2Cr2O7, except for D. similis from a recovery period under food restriction. However, a lower Pb sensitivity was seen for both species throughout generations. Both species also showed that under food restriction neonates' sizes were larger than those kept under regular food, while reproduction was considerably reduced. Food restriction also generated opposite outcomes on both species, such as D. magna epigenetic changes and D. similis phenotypic acclimation to Pb. Besides, D. magna pre-exposed to Pb presented lower sensitivity to mancozeb, while the contrary was shown by D. similis. This study indicates that daphnids are capable of acquiring a lower sensitivity to Pb across a long-term exposure, and that Pb pre-exposure can affect the sensitivity to other chemicals. Also, different patterns in multi-generational responses from monophyletic species (especially under oligotrophic media, common on natural habitats) acknowledge the use of representative or native species to assess the effect of contaminants, since monophyletic species can provide different toxicity outputs. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Multi-generation; Daphnids; Metal; Fungicide; Acute toxicity; Body length